PtSe2 grown directly on polymer foil for use as a robust piezoresistive sensor - Duesberg, Georg (My University, 2019)
Robust strain gauges are fabricated by growing PtSe2layers directly on top of flexible polyimide foils. These PtSe2layers are grown by low-temperature, thermally-assisted conversion of predeposited Pt layers. Under applied flexure the PtSe2layers show a decrease in electrical resistance signifying a negative gauge factor. The influence ofthe growth temperature and film thickness on the electromechanical properties of the PtSe2layers is investigated. The best-performing strain gauges fabricated have a superior gauge factor to that of commercial metal-based strain gauges. Notably, the strain gauges offer good cyclability and are very robust, surviving repeated peel tests and immersion in water. Furthermore, preliminary results indicate that the stain gauges also show potential for high-frequency operation. This host of advantageous properties, combined with the possibility of further optimization and channel patterning, indicate that PtSe2grown directly on polyimide holds great promise for future applications.
Keywords: flexible polyimide foils; Transition metal dichalcogenides; PtSe2; Strain gauges; Electromechanical sensors; Piezoresistivity; Flexible electronics